Effect of SOX2 on osteogenic differentiation of dental pulp stem cells - Yuan, J.; Liu, X.; Chen, Y.; Zhao, Y.; Liu, P.; Zhao, L.; Han, W. (Cellular and Molecular Biology, 2017)
To explore the effect of SOX2 on osteogenic differentiation of dental pulp stem cells (DPSCs) and to develop a new method for facilitating osteogenic differentiation of DPSCs. SOX2-overexpressing human DPSCs (DPSCs-SOX2) were established through retrovirus infection. Differentiation was induced with osteogenic differentiation medium and further evaluated by alkaline phosphatase (ALP) staining and qPCR. Following the differentiation procedure, the mechanism of SOX2 on osteogenic differentiation of DPSCs was analyzed using genome RNA microarray and flow cytometry. The normal DPSCs, DPSCs-vector, and DPSCs-SOX2 were capable of osteogenic differentiation after 3-4 weeks of introduction and positive for ALP staining. Compared to DPSCs and DPSCs-vector, DPSCs-SOX2 exhibited higher levels of osteogenic gene expression (ALP, collagen I, Runx2, and osterix), indicating the superiority of DPSCs-SOX2 in osteogenic differentiation. Moreover, SOX2 overexpression resulted in the activation of the Hippo signal pathway and increased expressions of the BMPs family. SOX2 promotes the osteogenic differentiation of DPSCs by regulating the osteogenic genes and BMPs family, suggesting the therapeutic potential in bone repair.